National and sub-national sero-epidemiology of immunoglobulin G against SARS-CoV-2 in Iran in 2021 - Mohammadreza Azangou-Khyavy; Erfan Ghasemi; Narges Ebrahimi; Mohammad-Mahdi Rashidi; Mohsen Abbasi-Kangevari; Naser Ahmadi; Javad Khanali; Ameneh Kazemi; Arezou Dilmaghani-Marand; Yosef Farzi; Moein Yoosefi; Elham Abdolhamidi; et al. (PLoS ONE, 2025)
Multiple factors challenge PCR test results for COVID-19 infection, and only symptomatic cases have been tested. Thus, a population-based seroprevalence study was necessary to determine the extent of missed cases. The objective of this study was to achieve a realistic infection rate in Iran and probe into some explanations behind being infected or not. In this population-based cross-sectional study, 16,610 adults aged more than 25 with valid serology sample results from 31 provinces from February to April 2021 were included. According to the ELISA kits based on the N antigen of SARS-CoV-2, the seroprevalence of IgG against SARS-CoV-2 in Iran was 20.63% (19.71–21.56) and 16.25% (15.11–17.41) based on two different corrections. The age-standardized seroprevalence was relatively high among Kurdistan [30.29% (26.04–34.55) and 28.31% (23–33.61)] and West Azarbayejan [29.33% (24.85–33.8) and 27.11% (21.52–32.68)]. Smoking, higher education, being underweight, male, and single were protective factors, and higher daily interactions was a risk for seropositivity. It is evident that reported infection rates have been misleading. Furthermore, several intervenable factors can predict the risk of infection.